Enantiodivergent Synthesis of Halofuginone by Candida antarctica Lipase B (CAL-B)-Catalyzed Kinetic Resolution in Cyclopentyl Methyl Ether (CPME) - De Marchi, Elisa; Arnodo, Davide; Maffeis, Elia; Scarpi, Dina; Prandi, Cristina; Occhiato, Ernesto G. (SynOpen, 2021)
The synthesis of both enantiomers of a key intermediate in the synthesis of halofuginone was accomplished by a Candida antarctica lipase B (CAL-B)-catalyzed kinetic resolution of the corresponding racemate. When the resolution was carried out in the versatile solvent cyclopentyl methyl ether (CPME) using p-chlorophenylbutyrate (PCPB) as the acylating reagent, the highest enantiomeric ratio (E) values were measured, and highly enantioenriched (95% ee) compounds could be obtained in a single iteration. As an example, one of the two enantiomers was used as a starting material to prepare (+)-halofuginone in a three-step procedure.
Keywords: biocatalysis; lipase; kinetic resolution; halofuginone